Analysis of Lead Concentration and Public Awareness of Health Impact in Cinangka and Cinangneng Villages - Fatimah, Ratih; Susetyo, Budi; Ismail, Gunawan; Wibowo, Rimun; Hidayaturrahman, Haerul (Universitas Ibn Khaldun Bogor, 2025)
Lead is a highly toxic metal that occurs naturally in the environment, but its extensive use by humans has significantly increased exposure levels and the associated risks to human health. This study aims to assess lead concentration in soil contaminated by used lead acid batteries (ULABs) and to evaluate community knowledge regarding lead and its health impacts in the Cinangka and Cinangneng Villages. This research is descriptive in nature. The lead concentration data was obtained from the RPFLH records of Bogor Regency in 2023, with 125 measurement points in Cinangka Village and 13 points in Cinangneng Village. For the community knowledge aspect, a questionnaire was administered to 76 respondents using an accidental sampling method. The findings reveal that the highest lead concentrations in both Cinangka and Cinangneng Villages have surpassed the TK-A limit, with total concentrations of 7,093.80 mg/kg in Cinangka Village and 7,307.35 mg/kg in Cinangneng Village, classifying the land as B3 waste category 1. Furthermore, while general public knowledge about the impacts and classifications of used battery waste is relatively high, awareness regarding the locations of contamination, methods for avoiding exposure, and the direct pollution in their environment remains low.